Development of transmon qubits solely from optical lithography on 300 mm wafers. (20th March 2019) - Foroozani, N; Hobbs, C; Hung, C C; Olson, S; Ashworth, D; Holland, E; Malloy, M; Kearney, P; O'Brien, B; Bunday, B; DiPaola, D; Advocate, W; et al.
Abstract: Qubit information processors are increasing in footprint but currently rely on e-beam lithography for patterning the required Josephson junctions (JJs). Advanced optical lithography is an alternative patterning method, and we report on the development of transmon qubits patterned solely with optical lithography. The lithography uses 193 nm wavelength exposure and 300 mm large silicon wafers. Qubits and arrays of evaluation JJs were patterned with process control which resulted in narrow feature distributions: a standard deviation of 0.78% for a 220 nm linewidth pattern realized across over half the width of the wafers. Room temperature evaluation found a 2.8%–3.6% standard deviation in JJ resistance in completed chips. The qubits used aluminum and titanium nitride films on silicon substrates without substantial silicon etching. T 1 times of the qubits were extracted at 26–27 μ s, indicating a low level of material-based qubit defects. This study shows that large wafer optical lithography on silicon is adequate for high-quality transmon qubits, and shows a promising path for improving many-qubit processors.